Analysis of the Management of Facilities and Infrastructure at the Language Laboratory Manado State University - Delli Sabudu; Deitje A Katuuk; Viktory N J Rotty; Jeffry S.J Lengkong (Tadbir : Jurnal Studi Manajemen Pendidikan, 2021)
The purpose of this study was to determine the management of language laboratory infrastructure facilities, Language and Arts Faculty, Manado State University. This research is a qualitative descriptive study. Sources of research data are heads of laboratories and lecturers of subjects who use language laboratories. Data collection techniques using interview techniques, observation and documentation study. The data analysis technique used descriptive qualitative data analysis. The results showed that: 1) The need for language laboratory infrastructure has been prepared annually according to the needs; 2) the provision of language laboratory facilities and infrastructure has not been running optimally; 3) The use of language laboratory facilities has been running quite well. 4) inventory of language laboratory infrastructure has been carried out properly, in accordance with existing standard procedures; 5) the maintenance of language laboratory facilities has not run optimally due to the lack of laboratory assistants, resulting in less than optimal maintenance of laboratory facilities; 6) the elimination of language laboratory infrastructure facilities has been carried out in accordance with existing standard procedures.